Synthesis and characterization of porous carbon nanospheres from biomass derived compounds - Wattanakul, Titiporn; Buengkitcharoen, Lalita; Ausavasukhi, Artit (Bulletin of Applied Sciences, 2022)
This research studied a synthesis of porous carbon nanospheres prepared from biomass derived compounds, namely glucose, sucrose, glycerol and cellulose by hydrothermal process combined with high temperature activation. The porous carbon nanospheres have been synthesized successfully in various diameters by hydrothermal method. The particle size of the carbon nanospheres is easily tunable from 188 to 10000 nm by simply varying the biomass derived compounds type and solvent concentrations. Surface functional groups, morphology, porosity, thermal stability and pH of zero charge were characterized to describe adsorption property. The adsorption behaviors of three dyes (methylene blue, congo red and direct scarlet 4BS) onto this biomass derived porous carbon nanospheres were investigated in batch systems. The experimental findings showed that the removal efficiencies of three dyes onto porous carbon nanospheres were maximum at the initial solution pH of 7-9 (amount of adsorbed sorbate (qt) ~ 100 mg/g).